Dual-chamber differs from single-chamber microbial electrosynthesis in biogas production performance under low temperature (15℃). (October 2021) - Wang, Hui; Du, Hongxia; Xie, Haiyin; Zhu, Jiemin; Zeng, Shufang; Igarashi, Yasuo; Luo, Feng
Graphical abstract: Highlight: Acetoclastic pathway was most important in low-temperature MES. Methahnosarcina and Methanothrix were enriched in DC and SC reactor, respectively. Electroactive bacteria Syntrophomonas, Pseudomonas and Bacteroides were dominated. The single-chamber MES achieve acetate to acetyl-CoA by acetate-CoA ligase. The dual-chamber MES was by acetate kinase and phosphate acetyltransferase. Abstract: In this study, single-chamber and dual-chamber Microbial electrosynthesis (MES) with carbon fiber brushes as electrodes were operated at 15°C to compare and analyze the difference in methanogenic performance. Metatranscriptomic analysis showed that the relative abundance of electroactive microorganisms Syntrophomonas, Pseudomonas and Bacteroides in each group exceeded 90%, while the abundance of Geobacter was less than 4%. Acetoclastic methanogens Methahnosarcina was more enriched in dual-chamber MES (61.74% 70.42%), and Methanothrix showed higher abundance in single-chamber MES (33.44% 51.71%). Methahnosarcina and Methanothrix could interact with electroactive microorganisms to improve the electron transfer efficiency through direct interspecies electron transfer (DIET). Analysis of the methane metabolic pathways of low-temperature MES found acetoclastic pathway was domination, and single-chamber MES achieved acetate to acetyl-CoA through acetate-CoA ligase (EC: 6.2.1.1), whereas dual-chamber MES was by acetate kinase (EC: 2.7.2.1) and phosphate acetyltransferase (EC: 2.3.1.8). These results are beneficial to further research on the treatment of low-temperature wastewater.